Location-log: Bringing Online Shopping Benefits to the Physical World with Magnetic-based Proximity Detection - Zhang, Ben; Chen, Kaifei; Cheng, Yun; Liang, Chieh-Jan Mike; Jiang, Xiaofan; Zhao, Feng (International Workshop on Mobile Sensing, 2012)
We present the design, implementation, and evaluation of Location-log – a mobile phone and cloud based system that brings the benefits of online shopping to the physical world. By utilizing magnetic-based proximity detection technology, Location-log is able to obtain the physical proximity relationships between customers and shops in a reliable and convenient manner. Building on top of this data, Location-log performs data analysis and creates visualizations to provide benefits to both customers and shop owners. Customers carrying smartphones attached with a small dongle can receive targeted advertisements and enjoy many other location-based services while shop owners are able to obtain statistics about customer behavior and react in real-time. We evaluate our system by deploying Location-log in a real food court inside a busy shopping center over multiple days. Results show that Location-log is effective in providing online shopping benefits – customers can receive accurate targeted advertisement based on their visiting histories and current locations while customer behavior statistics and visualizations provide greater insights for the owners.